ATTENTIONALITY CONTROL AND ITS RELATIONSHIP TO MEMORY CAPACITY IN ACCURATELY PERFORMING THE SKILL OF RECEIVING THE SERVE IN VOLLEYBALL FOR FEMALE STUDENTS - Ass. Lec.: Noor Ayad Abbas; Lec. Dr. Maryam Abdulameer Rashid; Ass. Lec.: Noor jasmine mohammed (Proximus Journal Publishing, 2024)
The study aimed to identify the values of attentional control and its relationship to memory capacity in accurately performing the skill of receiving the serve in volleyball for female students. The research hypotheses are that there is a statistically significant relationship between attentional control and the accuracy of performing the skill of receiving the serve in volleyball for female students. There is also a statistically significant relationship between memory capacity and the accuracy of performing the skill of receiving the serve in volleyball for female students. The two researchers used the descriptive approach using the method of correlation relationships on a sample of first-year female students in the College of Physical Education and Sports Sciences for Girls / University of Baghdad, the two researchers conducted a measure of attentional control, a test of memory capacity, and a test of the accuracy of the skill of receiving the serve in a volleyball on the research sample. They used appropriate statistical methods to extract the results, and in light of the results, they reached a number of conclusions, including that attentional control has a role in improving the accuracy of the skill of receiving the serve in volleyball for female students. Attentional control is related to memory capacity, as memory capacity is limited in an individual. When faced with a lot of new information at a specific time, the learner will fail to make appropriate attentional preparations, and thus the learner’s attentional control will decrease, In light of the conclusions, the two researchers recommend the need to pay attention to measuring and evaluating the mental abilities represented by (attention and memory) among female students of the College of Physical Education and Sports Sciences, because it contributes to improving the skills aspect of female students
Keywords: Attentionality control; memory; receiving; volleyball